INTERPLAY BETWEEN ORAL HEALTH, SYSTEMIC COMORBIDITIES, AND THERAPEUTIC RESPONSE IN ALZHEIMER’S DISEASE: TOWARD AN INTEGRATED MODEL OF DEMENTIA CARE - Oana Cristina Cretu; Doriana Agop Forna; Cosmin Bida; Marius Cocu; Teona Tudorici; Magda Calina Bârlean; Andrei Georgescu; Corina Ciupilan; Razvan Branzan; Elena Rodica Popescu (Romanian Journal of Oral Rehabilitation)
"This study aimed to evaluate the prevalence and clinical impact of oral conditions such as xerostomia, angular cheilitis, dysgeusia, and poor oral hygiene in AD patients undergoing long-term treatment. Methods: A retrospective study was conducted on 82 patient records from a geriatric neurology unit, divided into two groups based on treatment duration (3–6 months vs. >6 months). Clinical data regarding oral symptoms were extracted, and statistical analysis was performed using chi-square and Fisher’s exact tests to assess associations between treatment duration and the prevalence of specific oral health conditions. Results: Xerostomia was significantly more prevalent in the long-term therapy group (69.6%) compared to the short-term group (41.7%) (p < 0.05). Angular cheilitis was also more common in the long-term group (34.7% vs. 13.9%), although statistical significance was borderline (p = 0.052). Dysgeusia and poor oral hygiene showed increased frequency in the long-term group but did not reach statistical significance. The results indicate a trend of cumulative impact on oral health with increasing treatment duration. Conclusion: Oral health complications are frequent and clinically relevant in AD patients undergoing long-term treatment. Integrated oral care, early screening, caregiver education, and multidisciplinary collaboration are essential to mitigate risks and maintain patient quality of life. This study supports the need for structured oral health protocols as a component of comprehensive dementia care."